Cellular Responses of Human Postural Muscle to Dry Immersion - Shenkman, Boris S.; Kozlovskaya, Inessa B. (Frontiers in Physiology, 2019)
One of spaceflight factors having a considerable effect on regulation in the human locomotor system is support withdrawal. In recent years several authors, including the authors of the present paper, have revealed afferent mechanisms controlling support perception and introduced the notion of the support afferentation system. The so-called “dry immersion” model which was developed in Russia allows to suspend subjects in water providing the simulation of the mechanical support withdrawal. The present review is a summary of data allowing to appreciate the value of the “dry” immersion model for the purposes of studying cellular responses of human postural muscle to gravitational unloading. These studies corroborated our hypothesis that the removal of support afferentation inactivates the slow motor units pool which leads to selective inactivation, and subsequent atony and atrophy, of muscle fibers expressing the slow isoform of myosin heavy chain (which constitutes the majority of soleus muscle fibers). Fibers that have lost a significant part of cytoskeletal molecules are incapable of effective actomyosin motor mobilization which leads to lower calcium sensitivity and lower range of maximal tension in permeabilized fibers. Support withdrawal also leads to lower efficiency of protective mechanisms (nitric oxide synthase) and decreased activity of AMP-activated protein kinase. Thus, “dry” immersion studies, have already contributed considerably to the gravitational physiology of skeletal muscle.